Cover - Suprayitno, Hitapriya (Journal of Infrastructure & Facility Asset Management, 2025)
The Role of Tourism Infrastructure in Tourism Development: A Literature Review Yervi Hesna, Helmi, Akhmad Suraji & Sari Lenggogeni Effect Of Water-Fly Ash-Cement Grouting On The Clayey Subgrade Soil Characteristics of The Tuban-Babat Lamongan-Gresik National Road Mohammad Jagad Sekar Langit, Trihanyndio Rendy Satrya, Ria Asih Aryani Soemitro & Vidi Ferdian Evaluation and Planning of Strong and Durable Roads Due to Overloaded Vehicle (Case Study : The National Road Bts. Kab. Konawe Utara/Kab. Konawe – Pohara) Reza Kurniawan, Indrasurya Budisatria Mochtar & Freddy Siagian Slope Stability Assessment Using Limit Equilibrium Method With Deterministic and Probabilistic Approach (Case Study : Mota'ain-Motamasin National Road, East Nusa Tenggara, Indonesia) Muhammad Zakki, Ria Asih Aryani Soemitro, Trihanyndio Rendy Satrya & Andria Muharami Fitra Gabion Wall Slope Stabilization for Pejagan – Prupuk Road Widening (STA 116+450) Andhika Kesuma, Yudhi Lastiasih, Ibnu Kurniawan & Deni Wiharjito